Educational options for children with medical needs - Capurso,Michele (PeerJ PrePrints, 2014)
Schooling is known to influence a wide range of economic, social and psychological aspects of people’s life, but children with medical needs are subject to school failure more often than their healthy peers. The aim of this paper is to review different school options available to the paediatrics community for the education of children with medical needs. Hospital school, home tuition and mainstream school re-entry are examined. Critical aspects for each type of solution are discussed. The provision and stability of adequate educational opportunities for children with medical needs represents an important area of collaboration between doctors, educators and parents for the prevention of long-term consequences of illnesses and therapies.
Keywords: Children with medical needs; school attendance; mainstreaming